Grassland vegetation of the Molinio‐Arrhenatheretea class in the NW Balkan Peninsula. Issue 3 (21st January 2014) - Šilc, Urban; Aćić, Svetlana; Škvorc, Željko; Krstonošić, Daniel; Franjić, Jozo; Dajić Stevanović, Zora; Chytrý, Milan
Abstract Questions How does the floristic composition of plant species of meadows and mesic pastures vary along a broad geographical gradient in the NW Balkans? How does the current phytosociological classification of the Molinio‐Arrhenatheretea vegetation differ among the NW Balkan countries? Location NW Balkans (Slovenia, Croatia, Bosnia and Herzegovina, Serbia). Methods 3635 relevés originally assigned to the class Molinio‐Arrhenatheretea were classified with a beta flexible method, and the crispness of classification was checked. DCA ordination with Pignatti indicator values and climate data were applied to show the influence of site conditions on species composition. Results The classification was best interpreted at the level of 13 clusters, but could also be interpreted at the level of three groups of clusters. The first division was according to geography and climate: the first and third groups were concentrated in the NW part, while the second was restricted to the eastern part of the study area. The most important variable was site moisture, followed by nutrients and altitude, which corresponded with a west–east direction. The first group was very diverse and included communities on the wettest and most nutrient‐rich sites (Potentillion anserinae, Cynosurion cristati, Calthion palustris, Molinion caeruleae, Molinio‐Hordeion). The second group comprised mesophilous continental grasslands (Trifolio‐Ranunculion pedati, Trifolion pallidi, Trifolion resupinati), while the third group consisted of grasslands from regions with abundant precipitation (Arrhenatherion elatioris, Deschampsion cespitosae, Pancicion serbicae, Triseto flavescentis‐Polygonion bistortae). Conclusions Our analysis can be used to unify different phytosociological classifications in different countries, also showing the transitional forms of well‐known Central European vegetation types that have a different floristic composition and ecology in the Balkans. This knowledge will enable classification of the same vegetation types in neighbouring Balkan countries that are less studied.